Tingkat Motivasi Wajib Pajak Untuk Patuh Peraturan Pajak Berdasarkan Tingkat Pendidikan - Fedrick Eben Ezer Sinaga; Mila Susanti (Jurnal Ekonomis, 2023)
To achieve the target set in tax revenue, one of the factors comes from taxpayer compliance. This must be supported by the motivation that arises from within and outside the taxpayer. Therefore, this study aims to determine the level of taxpayer compliance from the point of view of taxpayer motivation based on education level. The population in this study were individual taxpayers in Parongpong District. Sampling was done by convenience sampling and found as many as 100 respondents. The research analysis used is descriptive analysis, correlation, determination, significance and regression. This analysis is carried out after going through validity, reliability and normality tests. The results showed that at the junior high school, high school, and Strata 2 education levels, it was proven that taxpayer motivation was not able to make taxpayers obedient. However, it can be seen that the graduate level shows the results that motivation is able to become a variable that makes significant changes to taxpayer compliance.